If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(y + 7) + -10y(y + 2) = -10 Reorder the terms: 6(7 + y) + -10y(y + 2) = -10 (7 * 6 + y * 6) + -10y(y + 2) = -10 (42 + 6y) + -10y(y + 2) = -10 Reorder the terms: 42 + 6y + -10y(2 + y) = -10 42 + 6y + (2 * -10y + y * -10y) = -10 42 + 6y + (-20y + -10y2) = -10 Combine like terms: 6y + -20y = -14y 42 + -14y + -10y2 = -10 Solving 42 + -14y + -10y2 = -10 Solving for variable 'y'. Reorder the terms: 42 + 10 + -14y + -10y2 = -10 + 10 Combine like terms: 42 + 10 = 52 52 + -14y + -10y2 = -10 + 10 Combine like terms: -10 + 10 = 0 52 + -14y + -10y2 = 0 Factor out the Greatest Common Factor (GCF), '2'. 2(26 + -7y + -5y2) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(26 + -7y + -5y2)' equal to zero and attempt to solve: Simplifying 26 + -7y + -5y2 = 0 Solving 26 + -7y + -5y2 = 0 Begin completing the square. Divide all terms by -5 the coefficient of the squared term: Divide each side by '-5'. -5.2 + 1.4y + y2 = 0 Move the constant term to the right: Add '5.2' to each side of the equation. -5.2 + 1.4y + 5.2 + y2 = 0 + 5.2 Reorder the terms: -5.2 + 5.2 + 1.4y + y2 = 0 + 5.2 Combine like terms: -5.2 + 5.2 = 0.0 0.0 + 1.4y + y2 = 0 + 5.2 1.4y + y2 = 0 + 5.2 Combine like terms: 0 + 5.2 = 5.2 1.4y + y2 = 5.2 The y term is 1.4y. Take half its coefficient (0.7). Square it (0.49) and add it to both sides. Add '0.49' to each side of the equation. 1.4y + 0.49 + y2 = 5.2 + 0.49 Reorder the terms: 0.49 + 1.4y + y2 = 5.2 + 0.49 Combine like terms: 5.2 + 0.49 = 5.69 0.49 + 1.4y + y2 = 5.69 Factor a perfect square on the left side: (y + 0.7)(y + 0.7) = 5.69 Calculate the square root of the right side: 2.385372088 Break this problem into two subproblems by setting (y + 0.7) equal to 2.385372088 and -2.385372088.Subproblem 1
y + 0.7 = 2.385372088 Simplifying y + 0.7 = 2.385372088 Reorder the terms: 0.7 + y = 2.385372088 Solving 0.7 + y = 2.385372088 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-0.7' to each side of the equation. 0.7 + -0.7 + y = 2.385372088 + -0.7 Combine like terms: 0.7 + -0.7 = 0.0 0.0 + y = 2.385372088 + -0.7 y = 2.385372088 + -0.7 Combine like terms: 2.385372088 + -0.7 = 1.685372088 y = 1.685372088 Simplifying y = 1.685372088Subproblem 2
y + 0.7 = -2.385372088 Simplifying y + 0.7 = -2.385372088 Reorder the terms: 0.7 + y = -2.385372088 Solving 0.7 + y = -2.385372088 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-0.7' to each side of the equation. 0.7 + -0.7 + y = -2.385372088 + -0.7 Combine like terms: 0.7 + -0.7 = 0.0 0.0 + y = -2.385372088 + -0.7 y = -2.385372088 + -0.7 Combine like terms: -2.385372088 + -0.7 = -3.085372088 y = -3.085372088 Simplifying y = -3.085372088Solution
The solution to the problem is based on the solutions from the subproblems. y = {1.685372088, -3.085372088}Solution
y = {1.685372088, -3.085372088}
| 84x^2-20xy+12x= | | 2-2=-6n-14 | | (4+2w)(w)=160 | | -12+m+10=-2m-10-m | | 25=-6n-14 | | 52800=56375-150m | | 23=-6n-14 | | 52800=56375-150 | | 18x^8-12x^7-24x^4= | | AEB=4x+1 | | 0=-3.4x^2+23x | | 19Ln(x)=17 | | t-7=r+6 | | 5.7(x-4)=-0.3x+13.2 | | 19lnx=17 | | 9+x/3=2 | | 6(7x-2)=7(6x-7) | | 10x=0.536 | | 4x+6+3=16 | | 33-9n=24 | | 2(-1)+5+3(-1)-3=5(-1)+9 | | 2x+25=4x+11 | | 4x^2-15x+1=-7x+8 | | -3g+6=15 | | 31-9n=24 | | 42x-12=42x-49 | | 20-x=64+x | | 3-1-9n=24 | | 5x+1=5x-5 | | a^2=-14-9a | | 14c-35=7 | | 6n=21.33 |